Overview of Fat, Alcohol and Sodium Consumption Habits in Men Aged 25-55 Years in North Tapanuli Regency - Yusnan Maria Habeahan; Albiner Siagian; Fazidah Aguslina Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Hypertension is a condition of increased persistent blood pressure with a systolic pressure of 140 mmHg and a diastolic pressure of more than 90 mmHg. Hypertension can be triggered by unhealthy consumption habits such as consumption of foods containing high fat, drinking coffee, alcohol and smoking can stimulate constriction of blood vessels so as to increase blood pressure. This type of research is a quantitative analytic survey with a Cross Sectional design to find the relationship of risk factors affecting the occurrence of disease, this study was conducted to analyze the determinants of hypertension based on consumption habits (frequency of fat and sodium intake) and alcohol consumption in North Tapanuli Regency. Based on calculations using the Lemeshow formula, the minimum sample size required in this study was 93 with the addition of 10 percent. Thus, 103 samples were needed to achieve a confidence level of 95 percent. Measurement of the incidence of hypertension was obtained through direct measurement using a mercury spygmomanometer twice with a 5-minute measurement interval conducted by medical personnel. The incidence of hypertension can be categorized according to the Ministry of Health (2013), namely not hypertension if blood pressure ≤140/90 and hypertension if blood pressure >140/90. Based on the results of the study, it was found that there was an effect of alcohol consumption on the incidence of hypertension in men aged 22-25 years in North Tapanuli Regency. While the variables of fat and sodium consumption habits have no influence on the incidence of hypertension. Therefore, it is expected that each puskmesmas of North Tapanuli Regency can hold Posbindu PTM in an area that is easily accessible and close to the place of residence so that the implementation of counseling and Posbindu activities can be carried out properly, it is expected for families, to always provide encouragement, direction, motivation and guidance to other family members about the benefits and objectives of Posbindu PTM, so that they feel their health is cared for and they will use Posbindu PTM regularly. Farmers are expected to be able to organize good food consumption habits. By reducing the consumption of fat intake, sodium and reducing the amount of alcohol consumed.